Discurso fotográfico no Instragam : a cidade de Vitória sob o olhar de seus usuários - Bianchi, Ana Clara Magnago (2017)
This work analyses the production of images in the context of the new communication practices. This new practices, in the condition of a discourse, give birth to new forms for a Being make appropriation of territories, creating new ways of being inside a world and new territorialities. The purpose of this study is to comprehend how the images produced in the context of cyberculture proliferates and which territories of the city this images proliferates. We stablished two questions to answer here: what discourses about the city are built in the context of life experience, imagination, technological resources and photographic language; and which relations/experiences are stablished with the city and the new communicational processes that allows the creation of discursive buildings about the city. Our theoreticalmethodological references area aligned with the actor-network theory, the discourse analyzes, the studies about cyberculture and the studies about territorialities. We decided to focus on the social network called Instagram and the city of Vitória, capital of Espírito Santo, Brazil. We decided to Use a multimethodological approach that is aligned with the contributions of Big Data analyzes, discourse analyzes and content analyzes that allowed us to collect, organize and comprehend the data that is part of this work, 51,850 unique images indexed with the hashtags #vix, #vitoriaes, #vitorinha and #vitoriasualinda. We built a theoretical body that allowed us to comprehend how the informational and physical territories constitutes the contemporary cities, the algorithms cities, creating a new links with the place. From the photos of our data, we perceived two dynamics of discursive production about the city of Vitória inside Instagram: one that starts from given ideas, the interdiscourse; and other that innovates, the intradiscourse. The production of photographic discourse about the city inside Instagram acquire, at the same time, new and updated outlines as new actors fights over producing meaning of a city, in this case Vitória. At the same time, this meaning production reinforce the synthesis images of the city, made inside the context of history and advertising speech, and produce innovation, making space for new relations with the city